Campanian ammonites from the Annona Chalk near Yancy, Arkansas - Kennedy, W; Cobban, W (1993)
Ammonites are abundant in the phosphatic base of the Annona Chalk (Campanian) near Yancy in Hempstead County, Arkansas. Twelve species are described. The diverse Nostoceras association is typical of Gulf Coast upper Campanian rocks but Didymoceratoides is a Western Interior upper middle Campanian genus. Nostoceras (N.) monotuberculatum n.sp., however, is known from a single specimen from the basal upper Campanian Didymoceras stevensoni zone in Colorado. -from Authors